Evaluation of the Thermo Scientific™ SureTect™ Listeria species Assay. (27th November 2019) - Cloke, Jonathan; Evans, Katharine; Crabtree, David; Hughes, Annette; Simpson, Helen; Holopainen, Jani; Wickstrand, Nina; Kauppinen, Mikko
Abstract: The Thermo Scientific™ SureTect™ Listeria species Assay is a new real-time PCR assay for the detection of all species of Listeria in food and environmental samples. This validation study was conducted using the AOAC Research Institute (RI) Performance Tested Methods SM program to validate the SureTect Listeria species Assay in comparison to the reference method detailed in International Organization for Standardization 11290-1:1996 including amendment 1:2004 in a variety of foods plus plastic and stainlesssteel. The food matrixes validated were smoked salmon, processed cheese, fresh bagged spinach, cantaloupe, cooked prawns, cooked sliced turkey meat, cooked sliced ham, salami, pork frankfurters, and raw ground beef. All matrixes were tested by Thermo Fisher Scientific, Microbiology Division, Basingstoke, UK. Inaddition, three matrixes (pork frankfurters, fresh bagged spinach, and stainless steel surface samples) were analyzed independently as part of the AOAC-RI-controlled independent laboratory study by the University of Guelph, Canada. Using probability of detection statistical analysis, a significant difference infavour of the SureTect assay was demonstrated between the SureTect and reference method for high level spiked samples of pork frankfurters, smoked salmon, cooked prawns, stainless steel, and low-spiked samples of salami. For all other matrixes, no significant difference was seen between the two methods during the study. Inclusivity testing was conducted with 68 different isolates of Listeria species, all of which were detected by the SureTect Listeria species Assay. None of the 33 exclusivity isolates were detected by the SureTect Listeria species Assay. Ruggedness testing was conducted to evaluate the performance of the assay with specific method deviations outside of the recommended parameters open to variation, which demonstrated that the assay gave reliable performance. Accelerated stability testing was additionally conducted, validating the assay shelf life.